2010
DOI: 10.1177/0022034510373764
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Expression and Accelerated Tooth Movement

Abstract: A supplemental appendix to this article is published electronically only at http://jdr.sagepub.com/supplemental. ABSTRACT It has been shown that inhibiting the expression of certain cytokines decreases the rate of tooth movement. Here, we hypothesized that stimulating the expression of inflammatory cytokines, through small perforations of cortical bone, increases the rate of bone remodeling and tooth movement. Forty-eight rats were divided into 4 groups: 50-cN force applied to the maxillary first molar (O), fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
169
2
12

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(195 citation statements)
references
References 33 publications
12
169
2
12
Order By: Relevance
“…In a previous animal study by Teixeira et al,11 orthodontic tooth movement on day 28 after three micro-osteoperforations with flap surgery in experimental rats was 2.13 times faster than in the control group. Baloul et al 8 reported that tooth movement was 1.3 times faster on day 42 after 10 microosteoperforations with flap elevation in rats.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In a previous animal study by Teixeira et al,11 orthodontic tooth movement on day 28 after three micro-osteoperforations with flap surgery in experimental rats was 2.13 times faster than in the control group. Baloul et al 8 reported that tooth movement was 1.3 times faster on day 42 after 10 microosteoperforations with flap elevation in rats.…”
Section: Discussionmentioning
confidence: 72%
“…9 In previous studies, some showed no significant improvement after the surgical operations, 10 whereas others showed significant acceleration in tooth movement. 8,9,11 However, the results are not comparable because the surgical approaches used in these studies were different. Some researchers have performed mucoperiosteal flap elevation but some have not.…”
Section: Introductionmentioning
confidence: 95%
“…The survival, fusion, and activation of osteoclasts correlates with the IL-1b level, which also determines the amount of tooth movement, as IL-1b regulates alveolar bone remodeling. 8 However, studies on the response of mediators of bone remodeling to the combination of vibratory stimuli and orthodontic force are still lacking; such research may help to explain how vibratory stimuli affects tooth movement. Analysis of gingival crevicular fluid (GCF) is a useful, noninvasive method for investigating changes in the levels of signal molecules, especially in vivo studies.…”
Section: Introductionmentioning
confidence: 99%
“…Bone remodelling is a process of both bone resorption on the pressure site and bone formation on the tension site 9. Orthodontic tooth movement can be controlled by the size of the applied force and the biological responses from the PDL .The force applied on the teeth will cause changes in the microenvironment around the PDL due to alterations of blood flow 10 , leading to the secretion of different inflammatory mediators such as cytokines, growth factors, neurotransmitters, colony-stimulating factors, and arachidonic acid metabolites 11 . As a result of these secretions, remodelling of the bone occurs .The most important growth factor is vascular endothelial growth factor (VEGF), this protein is a member of the PDGF/VEGF growth factor family and encodes a protein that is often found as a disulfide linked homodimer.…”
Section: Introductionmentioning
confidence: 99%